Perancangan Sistem Informasi E-Learning pada SMAN ABC - Zaki Baihaki, TB E; Nurmiati, Evy (Jurnal Transformatika, 2021)
The Covid-19 pandemic requires schools to divert their learning in their respective homes simultaneously with government regulations related to large-scale social access (PSBB) which aim to avoid crowds and add new clusters in the educational environment. This is a challenge for schools that do not yet have a bold learning platform and for teachers who still cannot use technology to provide their learning boldly. The web-based e-learning platform is expected to be able to assist teachers and students in carrying out learning without any technical guidance on its use. By using Rapid Application Development (RAD) in its design, it is hoped that it can produce an e-learning platform that is easy to use by teachers and students from SMAN ABC. This research is only up to the Design Workshop.
Keywords: E-Learning; RAD